2004
DOI: 10.1016/j.physb.2003.09.267
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure X-ray diffraction study of UMn2Ge2

Abstract: Uranium manganese germanide, UMn 2 Ge 2 , crystallizes in body-centered tetragonal ThCr 2 Si 2 structure with space group I4/mmm, a = 3.993Å and c = 10.809Å under ambient conditions. Energy dispersive X-ray diffraction was used to study the compression behaviour of UMn 2 Ge 2 in a diamond anvil cell. The sample was studied up to static pressure of 26 GPa and a reversible structural phase transition was observed at a pressure of ∼16.1 GPa. Unit cell parameters were determined up to 12.4 GPa and the calculated c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…The full lines represent linear fits to the present data; the dashed lines indicate the values a crit1 = 4.06 Å and a crit2 = 4.02 Å as discussed in the text. (c) The calculated chemical pressure based on the values of B 0 = 73.5 GPa and B0 = 11:4 for UMn 2 Ge 2 as a function of Y content. The full line is a guide to the eye.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The full lines represent linear fits to the present data; the dashed lines indicate the values a crit1 = 4.06 Å and a crit2 = 4.02 Å as discussed in the text. (c) The calculated chemical pressure based on the values of B 0 = 73.5 GPa and B0 = 11:4 for UMn 2 Ge 2 as a function of Y content. The full line is a guide to the eye.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to PrMn 2 Ge 2 as the reference, we consider the influence of the reduction in unit cell volume due to Y substitution to be analogous to the effects of “chemical pressure.” The Murnaghan equation of state and the experimental unit cell volumes of Pr 1− x Y x Mn 2 Ge 2 can be used to derive the related “chemical pressure.” It is accepted that the Murnaghan equation can be described as P(V)=B0B0V0VB01, where B 0 is the isothermal bulk modulus, B0 is its pressure derivative, and V 0 and V are the volumes at ambient pressure and pressure p , respectively. Using the values of B 0 = 73.5 GPa and B0=11.4 from the closely related compound UMn 2 Ge 2 , the equivalent “chemical pressure” from Pr 1− x Y x Mn 2 Ge 2 compounds can be derived as shown in Fig. c.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a perpendicular direction to c-axis, U atoms form planes at z = 0 and 1/2 that are interlayered by Mn 2 Ge 2 groups containing Mn at z = 1/4 and 3/4 on one hand and Ge at z ≈ ±0.375 and ±0.125 on the other hand. High pressure X-ray diffraction measurements [4] show that the compression along c is slightly more (3.7%) compared to compression along a (2.5%). Table 1 shows the pressure dependence of the lattice constants which were utilized in our band structure calculations.…”
Section: Crystal Structurementioning
confidence: 96%
“…Hence, it is appropriate to study this system as a function of external pressure, wherein one could observe the effects of changed inter-atomic distance keeping the 3d electron concentration unaltered. Earlier, high pressure X-ray diffraction studies on UMn 2 Ge 2 have shown that the structure remains stable up to a pressure of 12 GPa and the values of the bulk modulus and its pressure derivative obtained indicate that the degree of itinerancy of 5f states is much less as compared to other uranium compounds [4]. It was also proposed therein that with increasing pressure, hybridization effects would start dominating and lead to decrease of magnetic moments.…”
Section: Introductionmentioning
confidence: 94%